Evaluating the Integrated Disease Surveillance and Response system in Sidama Region, Ethiopia: A systems evaluation - Sileshi Demelash Sasie; Getinet Ayano; Fantu Mamo Aragaw; Mark Spigt (PLoS ONE, 2026)
Background Integrated Disease Surveillance and Response (IDSR) systems play a vital role in early detection and response to public health threats. In Ethiopia, limited evaluations exist on the effectiveness of IDSR at subnational levels. This study assessed the implementation of the IDSR system in Sidama Region to identify performance gaps and inform improvements. Methods A cross-sectional evaluation was conducted between September and November 2023 in Sidama Region, Ethiopia. A multistage cluster sampling technique was used to select 140 participants from 13 districts, public and private health facilities, health posts, and community health workers, including members of the Health Development Army (HDA). Data were collected using a structured checklist adapted from WHO and CDC guidelines. Key surveillance functions (e.g., case detection, reporting, data analysis) and supportive activities (e.g., training, supervision, logistics) were assessed. Descriptive statistics were generated using SPSS version 25. Using a priori thresholds from WHO IDSR and Ethiopian PHEM standards (≥90% adherence for formal facilities, ≥ 80% for community actors), we evaluated performance across all levels. Results Substantial variation was observed in the use of standardized case definitions, with adherence rates of 96% in public facilities, 67% in private facilities, 50% in health posts, and 4.17% among HDA members. This represents an 89-percentage-point gap between public facilities and community-level HDA members. All districts reported having rapid response teams; however, only 54% had budget lines dedicated to outbreak response. Surveillance data reporting forms were adequately available in only 15–23% of facilities, and only 61% of districts maintained emergency stockpiles. Training coverage and supervision frequencies varied, with significantly lower coverage among health posts and community-level actors. Only 11% of health posts and 12% of HDA members reported receiving relevant training. Thus, neither health posts nor HDA members met the predefined ≥80% training coverage benchmark. District-level facilities showed higher access to surveillance guidelines (92%) compared to 44% in public facilities and 50% in health posts. Complete reports were submitted by all private facilities (100%) but by only half of health posts (55%). Among HDA members, only 22% found data collection formats clear and easy to fill. Regarding surveillance system attributes, public and private facilities generally found case definitions easy to apply (85–93%), while only 37% of HDA members reported simplicity. Challenges with data quality, trend analysis, and procedural flexibility were frequently cited, particularly among lower-tier facilities. Acceptability of surveillance activities was high among public facilities (70%) but lower at district level (30%). At the community level, only 37% of HDA members found case definitions easy to apply, and just 22% rated reporting formats as usable. Conclusions The IDSR system in Sidama Region demonstrates uneven implementation across healthcare tiers, with notable disparities in training, supervision, data analysis, and resource availability. While district-level offices show relatively strong system components, lower-level facilities and community actors lack adequate support, compromising early detection and response capabilities. Strengthening training programs, harmonizing tools and guidelines, and improving logistics and digital infrastructure are critical for enhancing the overall effectiveness of Ethiopia’s disease surveillance system at the regional level.